Strategi Pengembangan UMKM Melalui Pelatihan Branding Dan Digital Marketing Dalam Peningkatan Pemasaran Produk Di RW 09 Kelurahan Menur Pumpungan - Dhea Amelia Putri Kamila; Roziana Febrianita; Vannia Angelita Yuniar Putri (BADAN PENERBIT STIEPARI PRESS, 2023)
The impact of technological developments on the structure of human life is so broad that it has contributed to making changes in various fields, one of which is the economic field. MSMEs as one of the business categories in the economic field are also required to keep abreast of technological developments in order to be able to expand product marketing. MSMEs RW 09 Menur Pumpungan Village as a partner of the 77 KKNT group MBKM UPN